2016
DOI: 10.1103/physreva.94.053850
|View full text |Cite
|
Sign up to set email alerts
|

Chiral optical local density of states in a spiral plasmonic cavity

Abstract: We introduce a new paradigm: the chiral electromagnetic local density of states (LDOS) in a spiral plasmonic nanostructure. In both classical and quantum regimes, we reveal using scanning near-field optical microscopy (NSOM) in combination with spin analysis that a spiral cavity possesses spin-dependent local optical modes. We expect this work to lead to promising directions for future quantum plasmonic device development, highlighting the potentials of chirality in quantum information processing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Latest research showed that the nearfield imaging of local ODOS revealed the chirality and spindependent local modes of the spiral plasmonic cavity. [150] Besides, the imaging by dichroic sensitive cathodoluminescence (CL) nanoscopy provided the explanation for the origin of dichroic hotelectron transfer at the interface between chiral gold SRRs and wide gap semicon ductor. [151] Moreover, the timeresolved detection of plasmonic chiral structures can provide the dynamics of electrons, which can be achieved by the ultrafast pumpprobe technique.…”
Section: Discussionmentioning
confidence: 99%
“…Latest research showed that the nearfield imaging of local ODOS revealed the chirality and spindependent local modes of the spiral plasmonic cavity. [150] Besides, the imaging by dichroic sensitive cathodoluminescence (CL) nanoscopy provided the explanation for the origin of dichroic hotelectron transfer at the interface between chiral gold SRRs and wide gap semicon ductor. [151] Moreover, the timeresolved detection of plasmonic chiral structures can provide the dynamics of electrons, which can be achieved by the ultrafast pumpprobe technique.…”
Section: Discussionmentioning
confidence: 99%
“…Chirality also plays a significant role in the field of nanoplasmonics and metamaterials . In these research areas, strong chiroptical effects are generally desired, e.g., for photon‐spin selective light–matter interactions, polarization‐resolved imaging and detection, and negative refractive index materials and circular polarizers . However, chiral molecules can only offer very small chiroptical responses, due to the small interaction cross section between natural molecules and light.…”
Section: Introductionmentioning
confidence: 99%
“…Provided the coherence requirements for the BSW-coupled radiation leaking out of the cavity are satisfied, the diffraction mechanism for free-space vortex generation remains as reported in the text above. While cavities can be chiral themselves, with a handedness-depending Local Density of States, 51 it has been recently shown that chiral plasmonic structures can foster sources located on their surface to radiate according to a specific circular polarization handedness. 52 These strategies provide an unprecedented degree of control on the polarization state of the emitted light.…”
Section: Discussionmentioning
confidence: 99%